Cabazitaxel-Induced Stabilization of Microtubules Enhances Radiosensitivity in Ovarian Cancer Cells - Kunos, Charles; Stefan, Tammy; Jacobberger, James W. (Frontiers in Oncology, 2013)
Background: Up to 40% of women with ovarian cancer have short disease-free intervals due to molecular mechanisms of chemotherapy resistance. New therapeutic strategies are sought. Ovarian cancers are sensitive to radiochemotherapy. The taxane cabazitaxel (XRP6258, Jevtana) promotes tubulin assembly and stabilizes microtubules against depolymerization in cells, acting similarly in mechanism to paclitaxel. Here, sequences of cabazitaxel-radiation co-administration are tested for drug-alone cytotoxicity and optimal radiosensitization. Methods: SKOV3, OVCAR3, and TOV-112D ovarian cancer cells were administered cabazitaxel 24 h before (first), 18 h before (second), together (third), or 24 h after (fourth) a single radiation dose, and then, investigated by clonogenic assay and flow cytometric assays. Radiation dose-cell survival data were fitted by two-stage multivariate analyses of variance. High content flow cytometry partitioned cabazitaxel effects into G2-phase versus M-phase events by DNA content, cyclin A2, and phospho-S10-histone H3 (PHH3). Paclitaxel served as a comparator. Findings: Cabazitaxel cytotoxicity and radiosensitization were dose dependent. Cabazitaxel added 24 h before radiation was the most lethal schedule. DNA content measurements by flow cytometry showed that cabazitaxel-treated cells accumulated in the radiosensitive G2/M 4C DNA complement compartment. Cytometry also showed that surviving cabazitaxel-induced cell cycle arrested cells resolve the arrest by entering 4C or by 8C DNA complement cell cycles. Interpretation: The radiosensitizing effect of cabazitaxel was schedule dependent, due to cell cycle redistribution, and best when cabazitaxel was given 24 h before radiation. Clinical trials of administering both cabazitaxel and radiation should be explored in women with chemoresistant ovarian cancer. Funding: Case Comprehensive Cancer Center and Sanofi-Aventis